Turkish peoples in the Byzantine Empire from 1025 to 1097 - Dudek, Jarosław (Balcanica Posnaniensia. Acta et studia, 2007)
The author of the article addresses the issue of Byzantium's relations with the Turkish tribes that migrated to the Balkans and Asia Minor in the 11th century. This phenomenon, comparable to earlier migrations, had far-reaching political, military and social consequences for the Empire. The background to the study is the situation after the death of Basil II, when the Byzantine state was forced to confront new nomadic communities – the Pechenegs, Oghuz, Polovtsians and Seljuks – which had varying effects on its structures. The aim of the article is to present the strategies used by Byzantium towards the Turkic peoples, with particular emphasis on diplomatic, military and assimilationist activities. Based on Byzantine sources, Armenian and Russian accounts, supplemented by the results of prosopographic and archaeological research, the author analyses the defence mechanisms and attempts to integrate the incoming groups. These included Christianisation, the granting of offices and the inclusion of elites in administrative and military structures. The main findings indicate that Byzantium's policy towards Turkish nomads had mixed results. In the Balkans, the Pechenegs and Oghuz were partially assimilated, while in Asia Minor, the Islamised subjects of the Seljuks led to destabilisation.